2020
DOI: 10.1177/1938640020948667
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the “Clinical Tibiofibular Line” Technique for Open Syndesmosis Reduction Assessment

Abstract: Background: When intraoperative computed tomography (CT) is unavailable, open syndesmosis assessment is a universally available, safe alternative that is more accurate than radiographic assessment. However, it has a documented malreduction rate of up to 16%. This may be improved upon with a validated technique for assessing the accuracy of open syndesmosis reductions. The “tibiofibular line” (TFL) is a CT-based technique found to be sensitive for malreduction. The purpose of this study was to assess the feasib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…126 The "tibiofibular line" (TFL) is a CT-based technique found to be sensitive to malreduction and in one recent study, it was shown that CT based TFL can be effectively translated into a reliable open technique. 127 The accuracy of the achieved reduction should be verified by comparing it with perfect mortise and lateral view of the opposite uninjured side, which is used as a template in the operating room. 128 Arthroscopy is another method used to identify instability as well as verify reduction.…”
Section: Operative Treatmentmentioning
confidence: 99%
“…126 The "tibiofibular line" (TFL) is a CT-based technique found to be sensitive to malreduction and in one recent study, it was shown that CT based TFL can be effectively translated into a reliable open technique. 127 The accuracy of the achieved reduction should be verified by comparing it with perfect mortise and lateral view of the opposite uninjured side, which is used as a template in the operating room. 128 Arthroscopy is another method used to identify instability as well as verify reduction.…”
Section: Operative Treatmentmentioning
confidence: 99%